John Boardman, A Classical Archaeologist’s Life: The Story So Far. An Autobiography - Osborne, Robin (Journal of Greek Archaeology, 2021)
John Boardman’s contribution to Classical Archaeology has been prodigious. The list of publications at the end of this autobiography admits to 44 books (14 of which have been translated, most of them into more than one language), 18 joint books (4 of them translated), about 10 edited books (plus 7 years as editor of JHS, editor for 17 BSA Supplements, joint editor for 20 issues of OJA and for LIMC and ThesCRA, and major editorial roles for CVA and Kerameus), and some 280 articles, with more listed as forthcoming and something published in every year from 1954 to 2016. It is hard to think that this is a record that will ever be surpassed.